Esports Research: A Literature Review - Reitman, J. G.; Anderson-Coto, M. J.; Wu, M.; Lee, J. S.; Steinkuehler, C. (Games and Culture, 2020)
Accompanying esports` explosion in popularity, the amount of academic research focused on organized, competitive gaming has grown rapidly. From 2002 through March 2018, esports research has developed from nonexistent into a field of study spread across seven academic disciplines. We review work in business, sports science, cognitive science, informatics, law, media studies, and sociology to understand the current state of academic research of esports and to identify convergent research questions, findings, and trends across fields.